2014
DOI: 10.17796/jcpd.38.3.83121661121g6773
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal Response to Nano Hydroxyapatite, Mineral Trioxide Aggregate and Calcium Hydroxide when Used as a Direct Pulp Capping Agent: An in Vivo study

Abstract: Nano hydroxyapatite (Nano-HA) and Mineral Trioxide Aggregate (MTA) because of its better qualities can be used as an alternative to calcium hydroxide in direct pulp capping procedures. The aim of the study was to compare the response of exposed human pulp to Nano-HA, Mineral Trioxide Aggregate and calcium hydroxide. Study design: The study was done on 30 premolars, ranging from patients between 11-15 years. Intentional pulp capping was done using one of the experimental materials. The extracted teeth were then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0
10

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 17 publications
4
38
0
10
Order By: Relevance
“…After 1 week, 2, 3, 4, and 6 months, MTA groups presented less inflammation, less hyperaemia, less necrosis, more frequent odontoblastic layer formation, and thicker dentinal bridging (0.19-0.43 mm for ProRoot, and 0.02-0.15 mm for Dycal from 3-6 months) than the calcium hydroxide group 23) . Another in vivo study also demonstrated that MTA caused less inflammation, less necrosis, and faster dentin bridge formation, than calcium hydroxide Dycal 28) . An in vitro study from the same paper demonstrated that calcium hydroxide (29.4% decrease of cell metabolic activity) caused higher cytotoxic effects to the MDPC-23 cells than MTA (9.9% decrease) 27) .…”
Section: Calcium Silicates and Resin-modified Calcium Silicatesmentioning
confidence: 93%
“…After 1 week, 2, 3, 4, and 6 months, MTA groups presented less inflammation, less hyperaemia, less necrosis, more frequent odontoblastic layer formation, and thicker dentinal bridging (0.19-0.43 mm for ProRoot, and 0.02-0.15 mm for Dycal from 3-6 months) than the calcium hydroxide group 23) . Another in vivo study also demonstrated that MTA caused less inflammation, less necrosis, and faster dentin bridge formation, than calcium hydroxide Dycal 28) . An in vitro study from the same paper demonstrated that calcium hydroxide (29.4% decrease of cell metabolic activity) caused higher cytotoxic effects to the MDPC-23 cells than MTA (9.9% decrease) 27) .…”
Section: Calcium Silicates and Resin-modified Calcium Silicatesmentioning
confidence: 93%
“…Previous studies have introduced various direct pulp-capping agents, such as hydroxyapatite 7) , tri-calcium phosphate (TCP) 8) , mineral trioxide aggregate (MTA) 7,9,10) , and emdogain (EMD) 9) . MTA, in particular, has been shown to promote complete dentin bridge formation without inducing inflammatory response in the pulp 7,9,10) . However, it also has limitations, such as high cost and difficult in handling compared to other pulp capping materials.…”
Section: Introductionmentioning
confidence: 99%
“…In clinical endodontics especially root canal and restorative treatments we can see the near future potential of nanoparticles from the application of nanoparticles in the form of solutions for irrigation, medication and as an additive within sealers/restorative materials [6]. GICs can be applied to base plates of Orthodontic and modified denture base well, as which contain chlorhexidine hexametaphosphate nanoparticles and characterize the nanoparticle size shows a stronger antimicrobial activity [7].…”
Section: The Nanomaterials Commonly Used In Dentistrymentioning
confidence: 99%
“…J Nanotechnol Nanomed Nanobiotechnol 4: 011. Nano HA which was used as a direct pulp capping agent, showed no inflammatory changes in majority of the samples in both the study periods, based on the ability of nano HA to produce complete dentinal bridges, favorable cellular and vascular response [6]. …”
mentioning
confidence: 91%
See 1 more Smart Citation